Webinar tentang Peningkatan Pengetahuan Remaja Putri Dalam Mengatasi Dismenore di Masa Pandemi COVID-19 - Nining Tunggal Sri Sunarti; Winarsih (J.Abdimas: Community Health, 2021)
Menstrual pain is a problem that often occurs in women. Many women experience menstrual problems, including pain during menstruation, known as dysmenorrhea. Dysmenorrhea affects 40% to 70% of women of reproductive age and is one of the most frequent causes of school absence. Research in the United States, dysmenorrhea is the leading cause of repeated absenteeism from school. Several studies have shown that adolescents with dysmenorrhea experience a decrease in academic achievement, social and sports activities. Service activities are carried out through webinar activities with the lecture method. A dedication to empowering young women in overcoming Dysmenorrhea in the COVID-19 Pandemic Period with 37 participants from the AKBIDYO Health Science College student. The activity was held on Sunday, July 18, 2021 which was presented through a webinar zoom meeting, because it was in the period of Enforcement of Community Activity Restrictions (PPKM). Activities can be carried out smoothly. The conclusion obtained: The knowledge of the youth participating in the webinar has increased by 4.17%. Most of the adolescent knowledge of the webinar participants was in the good category with a pre value of 79.16% and a post value of 83.33%. Suggestions for adolescents after receiving information about dysmenorrhea and how to overcome it, it is hoped that changes in attitudes and behavior will be more prepared in dealing with dysmenorrhea and for speakers to make scheduled and structured webinars that continue to focus on adolescents by looking at research and current issues.